Promotion of liver regeneration by natural killer cells in a murine model is dependent on extracellular adenosine triphosphate phosphohydrolysis12. Issue 5 (25th January 2013) - Graubardt, Nadine; Fahrner, René; Trochsler, Markus; Keogh, Adrian; Breu, Karin; Furer, Cynthia; Stroka, Deborah; Robson, Simon C.; Slack, Emma; Candinas, Daniel; Beldi, Guido
Abstract: Nucleotides, such as adenosine triphosphate (ATP), are released by cellular injury, bind to purinergic receptors expressed on hepatic parenchymal and nonparenchymal cells, and modulate cellular crosstalk. Liver resection and resulting cellular stress initiate such purinergic signaling responses between hepatocytes and innate immune cells, which regulate and ultimately drive liver regeneration. We studied a murine model of partial hepatectomy using immunodeficient mice to determine the effects of natural killer (NK) cell‐mediated purinergic signaling on liver regeneration. We noted first that liver NK cells undergo phenotypic changes post‐partial hepatectomy (PH) in vivo, including increased cytotoxicity and more immature phenotype manifested by alterations in the expression of CD107a, CD27, CD11b, and CD16. Hepatocellular proliferation is significantly decreased in Rag2/common gamma‐null mice (lacking T, B, and NK cells) when compared to wildtype and Rag1‐null mice (lacking T and B cells but retaining NK cells). Extracellular ATP levels are elevated post‐PH and NK cell cytotoxicity is substantively increased in vivo in response to hydrolysis of extracellular ATP levels by apyrase (soluble NTPDase). Moreover, liver regeneration is significantly increased by the scavenging of extracellular ATP in wildtype mice and in Rag2/common gamma‐null mice after adoptive transfer of NK cells. Blockade of NKG2D‐dependent interactions significantly decreased hepatocellular proliferation. In vitro, NK cell cytotoxicity is inhibited by extracellular ATP in a manner dependent on P2Y1, P2Y2, and P2X3 receptor activation. Conclusion : We propose that hepatic NK cells are activated and cytotoxic post‐PH and support hepatocellular proliferation. NK cell cytotoxicity is, however, attenuated by hepatic release of extracellular ATP by way of the activation of specific P2 receptors. Clearance of extracellular ATP elevates NK cell cytotoxicity and boosts liver regeneration. (HEPATOLOGY 2013)